Neural network dose prediction for rectal spacer stratification in dose‐escalated prostate radiotherapy. Issue 4 (11th March 2022) - Thomas, Christopher; Dregely, Isabel; Oksuz, Ilkay; Guerrero Urbano, Teresa; Greener, Tony; King, Andrew P.; Barrington, Sally F.
Abstract: Purpose: To develop a knowledge‐based decision‐support system capable of stratifying patients for rectal spacer (RS) insertion based on neural network predicted rectal dose, reducing the need for time‐ and resource‐intensive radiotherapy (RT) planning. Methods: Forty‐four patients treated for prostate cancer were enrolled into a clinical trial (NCT03238170). Dose‐escalated prostate RT plans were manually created for 30 patients with simulated boost volumes using a conventional treatment planning system (TPS) and used to train a hierarchically dense 3D convolutional neural network to rapidly predict RT dose distributions. The network was used to predict rectal doses for 14 unseen test patients, with associated toxicity risks calculated according to published data. All metrics obtained using the network were compared to conventionally planned values. Results: The neural network stratified patients with an accuracy of 100% based on optimal rectal dose–volume histogram constraints and 78.6% based on mandatory constraints. The network predicted dose‐derived grade 2 rectal bleeding risk within 95% confidence limits of ‐1.9% to +1.7% of conventional risk estimates (risk range 3.5%–9.9%) and late grade 2 fecal incontinence risk within ‐0.8% to +1.5% (risk range 2.3%–5.7%). Prediction of high‐resolution 3D dose distributions took 0.7 s. Conclusions: The feasibility of using a neural network to provide rapid decision support for RS insertion prior to RT has been demonstrated, and the potential for time and resource savings highlighted. Directly after target and healthy tissue delineation, the network is able to (i) risk stratify most patients with a high degree of accuracy to prioritize which patients would likely derive greatest benefit from RS insertion and (ii) identify patients close to the stratification threshold who would require conventional planning.